Recent Hearing Loss and Earache due to Bilateral Otitis Media associated with SARS-CoV-2 infection - Sahrish Ilyas; Samba Siva R Bathula (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2020)
Background: Since the outbreak began in late December 2019, COVID-19 has been declared a global pandemic, with over 3 million cases reported worldwide. COVID-19 is known to present commonly with symptoms such as fever, cough, shortness of breath, myalgias, loss of sense of taste and smell. Otalgia and hearing loss have been reported very rarely. We present a case of upper respiratory tract infection with involvement of the sinuses and middle ear secondary to SARS-CoV-2 infection.  Case report: A 69-year-old woman presented with fever, productive cough, bilateral earache, and diminished hearing for 5 days prior to admission. On examination, her temperature was 38.2 C, respirations 22/min, pulse rate 112/min, with O2 saturation of 96%. Otoscopy revealed erythema and opacification of the left tympanic membrane suggestive of otitis media. SARS-CoV-2 infection was confirmed by reverse transcription-polymerase chain reaction (RT-PCR) testing from nasopharyngeal swab. Chest x-ray revealed vascular congestion but no parenchymal opacities. A diagnosis of upper respiratory infection due to SARS-CoV-2 involving the sphenoid sinus and both middle ears was made based on head CT scan. Conclusion: COVID-19 most commonly presents with fever and respiratory symptoms, including cough, shortness of breath, anosmia, hyposmia, dysgeusia and sore throat. Involvement of the ear and sinuses from upper respiratory tract infection with SARS-CoV-2 has been previously reported in very limited case reports. We are presenting this case because we believe these findings should possibly alert clinicians to suspect SARS-CoV-2 infection and take proper protective measures to prevent the spread of infection.